2001
DOI: 10.1038/sj.onc.1204629
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the IL-13 receptor α2-chain by IL-4 and IL-13 in human keratinocytes: involvement of STAT6, ERK and p38 MAPK pathways

Abstract: IL-4 and IL-13 are related cytokines which induce both pro-and anti-in¯ammatory e ects depending on the cell type they act upon and the nature of the receptors expressed. The type I receptor complex is composed of the IL-4Ra and gc and only binds IL-4, whereas, in the type II receptor, IL-4Ra dimerizes with IL-13Ra1 upon either IL-4 or IL-13 binding. Another ligand binding chain potentially implicated in the IL-4/IL-13 receptor has been described, the IL-13Ra2, but the regulation of its expression and its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 39 publications
7
81
1
Order By: Relevance
“…1). These results are similar to studies by two other research groups, David et al (60) and Yasunaga et al (29), who found that the Th2 cytokines IL-4 and IL-13 induce IL-13R␣2 gene expression without affecting IL-13R␣1 and IL-4R␣. Ours is the first report showing that a lysophospholipid can regulate IL-13R␣2 expression.…”
Section: Discussionsupporting
confidence: 82%
“…1). These results are similar to studies by two other research groups, David et al (60) and Yasunaga et al (29), who found that the Th2 cytokines IL-4 and IL-13 induce IL-13R␣2 gene expression without affecting IL-13R␣1 and IL-4R␣. Ours is the first report showing that a lysophospholipid can regulate IL-13R␣2 expression.…”
Section: Discussionsupporting
confidence: 82%
“…The inability of IL-13R␣2 expression to confer IL-13 responsiveness despite high affinity binding, along with the finding of soluble IL-13R␣2 in vivo (9), has led to speculation that IL-13R␣2 is a decoy receptor. Expression of IL-13R␣2 varies across cell types and can be induced by inflammation and cytokines (15)(16)(17)(18)(19)(20). A role for IL-13R␣2 as a potential modulator of inflammation in asthma is suggested by the IL-13-and IL-4-dependent up-regulation of IL-13R␣2 in primary bronchial epithelial cells and the demonstration that overexpression of IL-13R␣2 in bronchial derived cells decreases IL-13-dependent Stat6 phosphorylation (21).…”
Section: Level Of Expression Of Il-13r␣2 Impacts Receptormentioning
confidence: 99%
“…STAT-6 is activated by the binding of IL-4 and/or IL-13 to the heterodimerized IL-4R␣:IL-13R␣1 (30). It then translocates to the nucleus where it inhibits the binding of NF-B to promoter sequences and subsequent gene expression (31).…”
Section: Effect Of Socs-1 and Socs-3 Is Regulated By Stat-6mentioning
confidence: 99%